Managing Contingent Liabilities Arising From Public Private Partnership Projects - Nwangwu, George (Journal of Sustainable Development Law and Policy, 2025)
All public infrastructure projects, irrespective of how they are procured, managed and financed, generate future liabilities. This becomes even more apparent under the Public Private Partnership arrangement. A number of these liabilities are subject to a high degree of uncertainty regarding when they will arise and the financial exposure involved when they do, and are therefore said to be contingent. Contingent liabilities have the potential to undermine national macroeconomic policy and cause significant economic harm when they crystalize. This article examines the legal and institutional mechanisms available in Nigeria to manage these liabilities and suggests ways for designing a PPP delivery process with inbuilt mechanisms for identifying, mitigating, tracking, and managing them.